2016
DOI: 10.1111/jav.00999
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fledging family space use in blue and great tit: similarities and species‐specific behaviours

Abstract: In birds, parental escorting of dependent young to feeding areas outside the breeding territory is a commonly observed, yet poorly documented phenomenon. Using radio-tracking, we provide a detailed description of the post-fledging movements of 12 blue tit Cyanistes caeruleus families and compare these observations with a much larger dataset of the closely related great tit Parus major collected over several years in the same study area. The proportion of families making excursions outside woodlots was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Fledglings and immatures show considerable movement in the post-breeding period before migration, a potential sign of prospecting for future breeding sites (Péron and Grémillet 2013;Brown and Taylor 2015;Vega et al 2016;Krüger and Amar 2017). On the other hand, breeding adults and their offspring often remain close (< 100 m) to their nest sites for less than 10 days after fledging (Streby and Andersen 2013;van Overveld et al 2017;Kysučan et al 2020). Therefore, the post-breeding social cues based on the density of adults and fledglings, or their proxies, such as fledgling call rates (Nocera et al 2006;Betts et al 2008;Kelly and Schmidt 2017) may be spatially accurate for only relatively short period of time.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Fledglings and immatures show considerable movement in the post-breeding period before migration, a potential sign of prospecting for future breeding sites (Péron and Grémillet 2013;Brown and Taylor 2015;Vega et al 2016;Krüger and Amar 2017). On the other hand, breeding adults and their offspring often remain close (< 100 m) to their nest sites for less than 10 days after fledging (Streby and Andersen 2013;van Overveld et al 2017;Kysučan et al 2020). Therefore, the post-breeding social cues based on the density of adults and fledglings, or their proxies, such as fledgling call rates (Nocera et al 2006;Betts et al 2008;Kelly and Schmidt 2017) may be spatially accurate for only relatively short period of time.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Improved tracking tools have allowed increased investigation of breeding bird movements in the less-studied fledgling and post-breeding stages, when adult movements are likely to be less predictable and wider ranging. For example, parents with dependent fledglings may expand their home range (Blakey et al 2020), alter habitat selection (Vitz and Rodewald 2006, Wohner et al 2020), or abandon their breeding territories (van Overveld et al 2017). Adults in the post-breeding period, when fledglings are no longer dependent, may show large-scale regional transition movements prior to actual migration (Brown and Taylor 2015, Bégin-Marchand et al 2022), make temporary long-distance excursions (Heggøy et al 2021, Curk et al 2022), and shift their home ranges to entirely new locations (Arlt and Pärt 2008, Cooper and Marra 2020).…”
Section: Introductionmentioning
confidence: 99%
“…to the study ofvan Overveld et al (2017), which showed that the spatial extent of families making excursions outside of their woodlot during the post-fledgling period is equal to 1100 m ± (SE = 265, range: 643-2374, n = 6) in blue tits and 666 m (SE = 42, range: 245-1898, n = 64) in great tits.Because of capture constraints due to the use of mist nets, most capture sites are settled in shrublands, woodlands with dense understorey or reedbeds(Eglington et al, 2015). Although this implies that very few sites are qualified as 'dense urban' or 'open farmland' in the dataset, it reflects well the distribution of habitats in France: A visual assessment was conducted to determine the correspondence between available habitats across France, encompassing both anthropization gradients, and habitats across sites, as depicted in FigureS1.3, with the results indicating a relatively close correspondence.…”
mentioning
confidence: 99%